2014
DOI: 10.1155/2014/864894
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Serum Exosomal MicroRNA-21 in Human Hepatocellular Carcinoma

Abstract: New strategies for the diagnosis of hepatocellular carcinoma (HCC) are urgently needed. There is an increasing interest in using microRNAs (miRNAs) as biomarkers in diseases. In this study, we examined the expression of miR-21 in serum exosomes from patients with HCC or chronic hepatitis B (CHB) and investigated the potential clinical significance of miR-21. Quantitative RT-PCR indicated that the concentration of miR-21 was significantly higher in exosomes than in exosome-depleted supernatants or the whole ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
220
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(233 citation statements)
references
References 26 publications
9
220
2
2
Order By: Relevance
“…Moreover, circulating exosomal miR-21 correlated with tumor HIFa expression, reflecting the hypoxic status of cancer. Our results were consistent with previous reports showing that serum exosomal miR-21 correlated with advanced tumor stage in hepatocellular carcinoma (48), esophageal squamous cell carcinoma (49), and laryngeal squamous cell carcinoma (50). These results provide novel evidence that circulating exosomal miR-21 may serve as a potential biomarker for the diagnosis and prognosis of many types of cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, circulating exosomal miR-21 correlated with tumor HIFa expression, reflecting the hypoxic status of cancer. Our results were consistent with previous reports showing that serum exosomal miR-21 correlated with advanced tumor stage in hepatocellular carcinoma (48), esophageal squamous cell carcinoma (49), and laryngeal squamous cell carcinoma (50). These results provide novel evidence that circulating exosomal miR-21 may serve as a potential biomarker for the diagnosis and prognosis of many types of cancer.…”
Section: Discussionsupporting
confidence: 92%
“…We examined whether miR transport from the heart to the plasma was altered with the onset of systolic RV failure, focusing on miR-21, since it showed high concentration in the plasma, was easily detectable, and its expression changed dramatically with disease progression, thereby giving it the greatest potential to serve as a biomarker. We began with an evaluation of exosome transport of miR-21 from cardiac fibroblasts to the bloodstream, similar to that described in hepatocellular carcinoma and other cancers (25). Plasma exosomes were identified via transmission electron microscopy imaging ( Figure 3F) and expressed CD63, a fibroblast-derived exosomal marker confirming the fibroblast origin of these exosomes ( Figure 3G).…”
Section: Model Of Pi+ps Recapitulates the Clinical Setting -Early Diamentioning
confidence: 70%
“…Importantly, miRNAs can be readily detected in small-volume samples using specific and sensitive quantitative real-time PCR (qRT-PCR) (68). Additionally, EV-associated miRNAs have been used as diagnostic and prognostic markers (20,(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79). Microarray analyses of miRNAs in EV-enriched fractions of serum from 88 patients with primary colorectal cancer (CRC) and 11 healthy controls revealed that that the levels of 7 miRNAs were significantly higher in the serum EVs of CRC patients compared with serum EVs from healthy donors (74).…”
Section: The Emerging Role Of Evs In Cancer Immunologymentioning
confidence: 99%